Community-based interventions for criminal offenders with severe mental illness - Fisher, William H. (Research in community and mental health ;, 2003)
People with mental illness in the criminal justice system are a vexing problem in many countries. Efforts to cope with this problem have taken a number of forms. Some focus on the expansion of existing community mental health treatment and support systems. Other, more recently developed approaches, such as jail diversion programmes and mental health courts, seek to move offenders with mental illness charged with "low-level" crimes from the criminal justice system to the mental health system. Others target offenders with mental illness who are being released from correctional settings, and attempt to facilitate their re-entry into the community and mental health service system. Whether and to what extent any of these efforts achieve their goals remains a significant question for researchers from a range of disciplines and for actors and stakeholders from various sectors of the mental health and criminal justice systems. The chapters presented in this volume explore key issues in this area, including the role of mental illness in criminal justice involvement, the effectiveness of psychopharmacologic and traditional community mental health treatment modalities, and the conceptualization and potential efficacy and effectiveness of new community-based approaches for serving offenders with mental illness.